KUALITAS BUTIR TES PILIHAN GANDA PADA PROGRAM KEAHLIAN TEKNIK GAMBAR BANGUNAN - Juliyanto Juliyanto; R Eka Murtinugraha; Riyan Arthur (Jurnal Pensil : Pendidikan Teknik Sipil, 2016)
Multiple choice test is generally used in midterm examinations, especially for the tenth grade students of Graphics Engineering in SMKN 1 Jakarta. Some of the subjects which use this type of test are Building Construction and Engineering Graphics. Nevertheless, the quality of each question of the tests has not been proven yet. Therefore, analysis towards the quality of each question on the test is needed. This research aims to know the quality of each question in multiple choice tests made by teacher for all subjects in civil engineering program SMKN 1 Jakarta. Qualitative descriptive method would be used in this research.The result of this research shows that Building Construction and Engineering Graphics have good content validity and construct validity, high reliability questions, proper difficulty levels (proportionally divided), effective tricky questions, and properly used bahasa Indonesia. Thus, hese multiple choice questions can be used as a reference in making other multiple choice questions for the next midterm examination week, under the condition that improvements are done throughoutly in order to achieve maximum result. To this point, it can be concluded that multiple choice questions, in graphics engineering program already have good quality.